Oxytocin facilitates social approach behavior in women - Preckel, Katrin; Scheele, Dirk; Kendrick, Keith M.; Maier, Wolfgang; Hurlemann, Rene (Frontiers in Behavioral Neuroscience, 2014)
In challenging environments including both numerous threats and scarce resources, the survival of an organism depends on its ability to quickly escape from dangers and to seize opportunities to gain rewards. The phylogenetically ancient neurohormonal oxytocin (OXT) system has been shown to influence both approach and avoidance (AA) behavior in men, but evidence for comparable effects in women is still lacking. We thus conducted a series of pharmacological behavioral experiments in a randomized double-blind study involving 76 healthy heterosexual women treated with either OXT (24 IU) or placebo intranasally. In Experiment 1, we tested how OXT influenced the social distance subjects maintained between themselves and either a female or male experimenter. In Experiment 2, we applied a reaction time based AA task. In Experiment 3 we investigated effects on peri-personal space by measuring the lateral attentional bias in a line bisection task. We found that OXT specifically decreased the distance maintained between subjects and the male but not the female experimenter and also accelerated approach towards pleasant social stimuli in the AA task. However, OXT did not influence the size of peri-personal space, suggesting that it does not alter perception of personal space per se, but rather that a social element is necessary for OXT’s effects on AA behavior to become evident. Taken together, our results point to an evolutionarily adaptive mechanism by which OXT in women selectively promotes approach behavior in positive social contexts.